Ultrastructure of Lejeunea spp. leaves surface in a lowland tropical urban forest of Universitas Indonesia Campus, Depok, Indonesia - Afiatry Putrika; Dhita Mutiara Nabella; Andi Salamah; Nisyawati NISYAWATI; Astari Dwiranti (Society for Indonesian Biodiversity, 2020)
Abstract. Putrika A, Nabella DM, Salamah A, Nisyawati, Dwiranti A. 2020. Ultrastructure of Lejeunea spp. leaves surface in a lowland tropical urban forest of Universitas Indonesia Campus, Depok, Indonesia. Biodiversitas 21: 4184-4191. Lejeunea is one of liverworts genera that have a wide distribution in the world. It has many variations of the character that have not been revealed, such as variations of the cell surface. The purpose of this research was to study the ultrastructure of Lejeunea spp. leaves surface in a lowland tropical urban forest of Universitas Indonesia (UI) Campus, Depok, Indonesia. Six species of Lejeunea spp. were studied, i.e., L. anisophylla, L. cocoes, L. exilis, L. papilionacea, L. catanduana, and L. curviloba. The research methods carried out in this study consisted of the sample observation using a light microscope, sample preparation for Scanning Electron Microscope (SEM) observation (fixation, post-fixation, dehydration, drying, mounting), and observations using SEM. The results of observation using a light microscope showed the smooth cell surface of all samples studied. Meanwhile, the differences between six species of Lejeunea in the UI campus could be differentiated under SEM. L. catanduana could be distinguished from other species from its cell wall thickness and texture, ornamentation types, and the number of ornamentations per cell. The texture of the cell wall of L. catanduana was the roughest than the other species due to abundant ornamentation such as papillae on its the cell wall surface. Furthermore, only this species has mamillae on the cell surface. The number of papillae or mamillae was 1-4 per cell. On the other hand, L. cocoes has the thinnest cell wall and slightly rough texture. Only this species has the simple papillae on the cell surface. Thus, the results of this study suggested that the cell surface variations in Lejeunea might be potential to be used as taxonomic characters in grouping species.